Peran E-Learning dalam Meningkatkan Fleksibilitas dan Prestasi Akademik Mahasiswa: Perspektif dari Kota Makassar - Rina Asriani J Tudon B; Nurwahyuni Paallo; Nurrahmah Agusnaya; Fajriani Azis; Andi Anggi Kemalasari (Journal of Vocational, Informatics and Computer Education, 2025)
The shift toward digital learning models has raised concerns about students' readiness and their perceptions of e-learning effectiveness in higher education. The aim of this study is to provide a solid foundation for educational institutions, lecturers, and universities in understanding students' awareness levels regarding information technology innovation. This research seeks to explore students' perceptions in Makassar City toward the use of e-learning within blended and online learning models, employing a quantitative approach with a cross-sectional design. The subjects or samples of this study are students from several universities located in Makassar City. The study utilized a questionnaire distributed to students at various universities in Makassar via Google Forms as the data collection instrument. Data analysis was conducted using descriptive statistics and linear regression techniques. The findings indicate that students in Makassar City have a positive perception of e-learning usage in the context of blended and online learning. This perception is based on their experiences in utilizing e-learning within such learning models. The study contributes to a deeper understanding of e-learning implementation in the context of modern education, particularly in efforts to enhance the quality of learning at the higher education level.